2011
DOI: 10.4248/ijos11077
|View full text |Cite
|
Sign up to set email alerts
|

Role of angiogenesis in oral squamous cell carcinoma development and metastasis: an immunohistochemical study

Abstract: Although a few studies have shown that vascularity is increased from normal mucosa to dysplasia to carcinoma suggesting that disease progression in the oral mucosa is accompanied by angiogenesis. The role in lymph node metastasis in oral squamous cell carcinoma (OSCC) is equivocal. Role of angiogenesis in OSCC development and metastasis is evaluated in this study. This retrospective study of 50 samples consisted of 9 normal buccal mucosa, 22 leukoplakias, and 19 OSCC. Polyclonal antibodies to von-Willebrand fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 40 publications
(46 reference statements)
4
20
0
Order By: Relevance
“…The purpose of angiogenesis in tumours is to sequester nutrients from the host for tumour cell survival and tumour growth (Carmeliet and Jain, 2000). Extensive studies pointed out that angiogenesis have been associated with tumour progression and aggressiveness in a number of malignancies, including oral cancer (Uehara et al, 2004;Shivamallappa et al, 2011). In the present study, we noticed over expression of VEGF in the buccal mucosa of hamsters treated with DMBA alone.…”
Section: Discussionsupporting
confidence: 61%
“…The purpose of angiogenesis in tumours is to sequester nutrients from the host for tumour cell survival and tumour growth (Carmeliet and Jain, 2000). Extensive studies pointed out that angiogenesis have been associated with tumour progression and aggressiveness in a number of malignancies, including oral cancer (Uehara et al, 2004;Shivamallappa et al, 2011). In the present study, we noticed over expression of VEGF in the buccal mucosa of hamsters treated with DMBA alone.…”
Section: Discussionsupporting
confidence: 61%
“…Members of the human epidermal receptor (HER) family including the EGFR and to a lesser extent HER2 and HER3 play key roles in driving the oncogenic pathways that are important for cancer cell growth and proliferation, survival, and angiogenesis. Increased expression of the epidermal growth factor receptor (EGFR) can play a critical role in oral tumor development and progression (Grandis and Tweardy 1993;Shivamallappa et al 2011), and EGFR increases progressively from oral premalignant lesions to invasive OSCC (Shin et al 1994). MMPs are a family of secreted proteins that remodel and digest the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…One study conducted on head and neck malignant tumors presented correlations between vessel density, bad prognosis and onset of metastases [33,34], while another study found no correlation between angiogenesis and tumor stage and prognosis [35]. It is still unclear whether these discrepancies due to different tumor stages, localization or methods of analysis [36].…”
Section: Discussionmentioning
confidence: 99%